PENGGUNAAN ABU SEKAM PADI SEBAGAI MATERIAL PENGGANTI PASIR PADA PENGUJIAN KUAT TEKAN BETON - Husainy, Zainuddin; Suryaningsih, Oktavia (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
The use of rice husk ash as a substitute material for sand with a percentage of rice husk ash addition of 5%, 7.5% and 10% with the aim of determining the optimal percentage of the use of rice husk ash from the volume of sand with concrete without using additional rice husk ash or normal concrete and the age of the planned concrete to be tested for compressive strength is 7 days, 14 days and 21 days. The results obtained from this test showed that the compressive strength value of normal concrete at the age of 7 days had reached the targeted average compressive strength as well as the ages of 14 and 21 days had achieved the desired results. While concrete with a mixture of rice husk ash at the age of 7 days at each percentage did not reach the targeted average value, the highest value obtained was 16.59 with a mixture of rice husk ash as much as 7.5% of the weight of the sand as well as at the age of concrete with a mixture of rice husk ash with a concrete age of 14 days has not reached the desired value with the highest value of 19.70 from 7.5% of the mixture of rice husk ash from the weight value of sand. While concrete with a mixture of rice husk ash at the age of 21 days only one percentage of the mixture of rice husk ash can reach the desired average value of 21.12 from 7.5% of the mixture of rice husk ash from the total weight of sand.